Influence of process parameters in Wire and Arc Additive Manufacturing (WAAM) process / Nor Ana Rosli...[et al.] - Rosli, Nor Ana; Alkahari, Mohd Rizal; Ramli, Faiz Redza; Sudin, Mohd Nizam; Maidin, Shajahan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
Wire and arc additive manufacturing (WAAM) has developed a wide range of processes and applications. This technology is a new approach to modern manufacturing and is gaining interest from the research community due to its ability to create affordable, large-scale components. Nevertheless, WAAM may affected by porosity, humping and undercut. These issues need to be addressed in a specific way to achieve desired quality that is comparable to the traditional processing technique. This article examines various weld travel speeds, where defects start appearing. The effects of travel speed and wire feed speed (WFS) were also discussed. It was found that, travel speed and WFS had a major influence on deposition width and height and a stable deposited layer was produced between heat input values of 0.2620 kJ/mm and 0.32756 kJ/mm.